The Use of First Language in General English Class of Non-English Major Students - Feny Martina; Liza Nurhasanah Lubis; Irwan Satria (Yayasan Karinosseff Muda Indonesia, 2023)
The objectives of this research are to examine how first languages are perceived in English language classes and to look at how both teachers and students use their first language in these types of situations. This research used a mixed-method approach, where both quantitative and qualitative research is undertaken. The type of data from this research was obtained from 2 data. Questionnaire data from 60 respondents. Interview data from 5 students and 1 lecturer. In this research, the researchers found (1) Students` perceptions of first language use in English class (2) Reasons why teachers and students use their first language in English class (3) The reasons teachers allow students to use first language in English class (4) Students'' reasons prefer to use the first language during the teaching and learning process. Language teaching not only embraces the use of first language (Indonesian) in EFL education, but is also considered a valuable resource that should not be neglected. English teachers must speak up against the excessive use of their first language. However, it can be put to good use in understanding new abstract words, assessing comprehension, giving instructions, and explaining grammar. Therefore, first language is once again in the spotlight, becoming a useful but neglected resource in EFL education.